Transplantation of Human-induced Pluripotent Stem Cell-derived Cardiomyocytes Is Superior to Somatic Stem Cell Therapy for Restoring Cardiac Function and Oxygen Consumption in a Porcine Model of Myocardial Infarction. Issue 2 (February 2019) - Ishida, Masaru; Miyagawa, Shigeru; Saito, Atsuhiro; Fukushima, Satsuki; Harada, Akima; Ito, Emiko; Ohashi, Fumiya; Watabe, Tadashi; Hatazawa, Jun; Matsuura, Katsuhisa; Sawa, Yoshiki
Abstract : Background: Somatic stem cell (SC) therapy can improve cardiac performance following ischemic injury. In this study, we investigated whether induced pluripotent SC-derived cardiomyocytes (iPS-CMs) are more effective than somatic SCs, such as skeletal myoblasts (SM) and mesenchymal (M)SCs, in promoting functional recovery upon transplantation in a porcine model of myocardial infarction. Methods: Myocardial injury was induced by ameroid ring placement in immunosuppressed female mini pigs; after 1 month, epicardial cell transplantation was performed with iPS-CMs (n = 7), SMs (n = 7), and MSCs (n = 7). Control pigs underwent sham operation (n = 8). Results: Cell therapy improved functional recovery 2 months after myocardial infarction, as evidenced by increased ejection fraction (iPS-CM, +7.3% ± 2.2% and SM, +5.8% ± 5.4% vs control, −4.4% ± 3.8%; P < 0.05). The analysis of regional contractile function in the infarcted zone revealed an increase in transverse peak strain (iPS-CM, +4.6% ± 2.2% vs control, −3.8% ± 4.7%; P < 0.05). The C-11 acetate kinetic analysis by positron emission tomography showed that the work-metabolic cardiac energy efficacy increased by the transplantation of iPS-CMs, but was reduced by the other cell types. This was accompanied by decreased myocardial wall stress in the infarcted zone (iPS-CM, −27.6 ± 32.3 Pa and SM, −12.8 ± 27 Pa vs control, +40.5 ± 33.9 Pa; P < 0.05). Conclusions: The iPS-CM is superior to other somatic cell sources in terms of improving regional contractile function and cardiac bioenergetic efficiency, suggesting greater clinical benefits in severely damaged myocardium. Abstract : The authors compare the therapeutic effects among human induced pluripotent stem cell-derived cardiomyocytes, skeletal myoblasts stem cells and mesenchymal stem cells on promoting cardiac functional recovery including regional contractile function and cardiac bioenergetic efficiency in a porcine model of myocardial infarction. Supplemental digital content is available in the text.